Environmental history and Memory : an evaluation of drought and dry periods in south-central and south -eastern Zimbabwe, 1940- present , and the archaeological implications - Pikirayi, Innocent (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2021.